Empowerment onderzoek: een kritische vriend voor sociaal werkers - Tine Van Regenmortel; Katrien Steenssens; Roos Steens (Journal of Social Intervention: Theory and Practice, 2016)
Empowerment research: A critical friend for social work practitioners The empowerment paradigm has consequences for social work practice and policy, as well as for the way in which research is carried out. The growing prominence of empowerment research is relevant because empowerment – as a central notion in the international definition of social work – provides identity to social work research. Empowerment research also meets the increasing demand for co-creation in research. Here, different stakeholders not only contribute relevant knowledge, but also have a say in the design of the research and in the interpretation and transfer of its results. The questions that we address in this article involve the methodological consequences of empowerment research, its implementation in practice and the lessons that can be learned from this.In the first part of this article, we demonstrate the theoretical foundations of empowerment research. In addition to its philosophical underpinnings, we describe the key aspects of empowerment research focusing particularly on methodological consequences. Three inspirational resources are the empowerment theory formulated by Rappaport and Zimmerman, responsive evaluation formulated by Stake and Abma, and empowerment evaluation formulated by Fetterman and Wandersman. We describe this threefold perspective, which is so central to empowerment research, as a power-oriented, multi-stakeholder and multi-level research approach, with a focus on improvement and social justice, a quest for ownership, continuous participation and dialogue, the acknowledgement of the equal value of three forms of knowledge and capacity building, learning organizations and shared responsibility.We also reflect on the unusual role of the researcher in empowerment research. Rather than being “the” expert as an outsider, who positions himself/herself above all other stakeholders, the researcher is “just” one of the parties involved, who, with his or her own specific expertise, searches for improvement together with the other stakeholders. It is about partnership. The researcher facilitates dialogue and mutual learning, he is a Socratic guide searching for common ground amidst the varying interests and perspectives of the stakeholders, and with particular consideration for the “silenced voices”. We label the role of the researcher as “critical friend”: someone who creates trust and also reveals something of himself or herself (the importance of reciprocity), but also provides mirrors, frameworks and ideas that foster critical reflection and development.In the second part of the article, we describe the practice of empowerment research. The concept of “Empowering Academic Collaborative Center” is a far-reaching interpretation of empowerment research. We use the following definition.An Empowering Academic Collaborative Center is a structural and long-lasting collaboration between one or more social practice organizations, one or more research organizations and users, which establishes and accomplishes scientific- and action-oriented research in the form of a co-creation by professionals, users, researchers and management  / policy, in order to improve the quality of the care and of the empowerment process of the stakeholders involved, especially of professionals and users.In Flanders, the initial experience with this innovative concept is situated in the fields of youth care and social work. We describe several meta reflections that are points of interest for the practice of empowerment research. A first reflection relates to the qualities of the empowerment researcher. The skills that he or she requires are of major importance and are located on three levels: the content level, the methodological level and the personal-social level. The researcher needs to be knowledgeable about the sector and the operation of the organization, as well as the subject of interest. The position of critical friend also requires a great deal of flexibility on the part of the researcher. In order to connect the different stakeholders and levels of the organization, he or she needs to be able to negotiate, make compromises and at the same time maintain the scientific quality of the research. The role of critical friend also requires the ability to listen and empathize, an attitude of respect and appraisal, multi-directed partiality and patience. A second reflection emphasizes the importance of dialogue and deliberation through transparent structures. These are necessary to connect the different stakeholders and allow an open discussion that can clarify tensions and identify clashing expectations. A third point of interest is the appointment of go-betweens in the organization, the “ambassadors”. This turned out to be crucial in creating sufficient support for the research in the organization and disseminating the results throughout the entire organization. A final point of interest is the participation of users and professionals. The involvement of users in empowerment research can vary considerably and is a gradual process. A blind choice for the highest step on the participation ladder is not advisable. It is necessary to take account of  the particularity of the organization and whether or not it already has a culture of participation. Depending on the subject of interest, it is possible that only professionals participate. This was the case in research on organizational empowerment in social work organizations, where a task force of representatives of the different functions in the organization was established.We conclude that empowerment research creates opportunities to examine complex social interventions with vulnerable groups. By engaging closely with the different stakeholders and building and working on a gradual process together with them, it is possible to obtain a  richer, more profound and “layered” picture of the complex practice of social work. At the same time, processes of change start at different levels of the organization. Professionals are involved in critical reflection, management learns to take account of the perspective of other stakeholders in its decisions, and users learn that their reflections and ideas, too, are used to improve practice. At the same time, it is necessary to continue to systematically map the critical factors and necessary conditions for empowerment research and the way in which its scientific validity can be made visible. It is important that science and practice are willing to view one another as partners and that this innovative method of collaboration between science, practice/policy and users is supported and encouraged by science policy. SAMENVATTING Empowerment onderzoek: een kritische vriend voor sociaal werkers Het empowermentparadigma heeft niet alleen gevolgen voor praktijk en beleid, maar ook voor de wijze van onderzoeken. In dit artikel worden in een eerste deel de theoretische grondslagen van empowerment onderzoek belicht. Naast de wetenschapsfilosofische basis beschrijven we de kernaspecten van empowerment onderzoek met extra aandacht voor methodologische consequenties. Drie inspiratiebronnen hiervoor zijn: de empowerment theorie van Rappaport en Zimmerman, responsieve evaluatie van Stake en Abma en empowerment evaluatie van Fetterman en Wandersman. We belichten als kern het drieledig perspectief: krachtgericht, multistakeholders en multilevel, de focus op verbetering en sociale rechtvaardigheid, het streven naar eigenaarschap, een continue participatie en dialoog, erkenning van drie gelijkwaardige kennisvormen en capaciteitsopbouw, lerende organisatie en gedeelde verantwoordelijkheid. We sluiten af met de rol van de onderzoeker als “kritische vriend”. In een tweede deel beschrijven we de praktijk van empowerment onderzoek. Na de toelichting van het concept van “Empowerende Academische Werkplaats” als doorgedreven invulling van empowerment onderzoek, beschrijven we eerste praktijkervaringen in Vlaanderen met dit innovatieve concept binnen de jeugdzorg. Aangevuld met nieuwe praktijkervaringen met empowerment onderzoek in de sociale sector in Vlaanderen, worden een aantal metareflecties beschreven. Deze reflecties hebben betrekking op de kwaliteiten van de empowerment onderzoeker, dialoog en overleg via transparante overlegstructuren, het belang van ambassadeurs binnen de organisatie en de participatie van de gebruikers en professionals. De eindbalans van deze praktijkervaringen met empowerment onderzoek is positief. Het uitgetekende kader voor empowerment onderzoek leent zich bij uitstek goed voor complexe sociale interventies met kwetsbare doelgroepen.